Characterization of oligostilbenes from bark and leaves of Neobalanocarpus heimii using ion trap LC-MS/MS" technique / Ratni Suriyani Jalal - Jalal, Ratni Suriyani (2015)
This thesis describes a novel method for the structural characterization of oligostilbenes based on high performance liquid chromatography combined with electrospray ionization ion trap multiple-stage mass spectrometry. Pure oligostilbenes as well as a standard heartwood extract from Neobalanocarpus heimii were analyzed using MS1 to MS5 positive ion mode. The MS" data of [M+H]+ ion of oligostilbenes were found to provide fragmentation patterns unique of each oligostilbene. The essential part of the reported method is the referencing of mass spectral data that allows for comparison of fragmentation patterns between different oligostilbenes based on multiple stage mass spectra. Fragmentation mechanisms were proposed for the most common fragmentation patterns. A pilot database including ESI-IT-MS" data for 11 oligostilbenes structures was established and used to dereplicate bark and leave extracts from Neobalanocarpus heimii. Components of these extracts were efficiently identified within a very short analysis time, thus demonstrating the power of this HPLC on-line coupled MS" approach. The method was evaluated with respect to available hardware and software and directions for further development were suggested.